2019
DOI: 10.22159/ajpcr.2020.v13i1.36028
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Adverse Drug Reactions in a Tertiary Care Hospital in South India

Abstract: Objective: The objective of this study was to determine the prevalence of adverse drug reactions (ADRs) in a tertiary care teaching hospital in South India and to analyze the causality according to the Naranjo scale. Methods: This study was carried out at the SRM Medical College, Chennai, a tertiary care hospital, which is an ADR monitoring center under Pharmacovigilance Programme of India, over a period of 1 year, from September 2017 to August 2018, after approval by the Institutional Ethics Committee. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
2
1
Order By: Relevance
“…In contrary to this study, urticaria forms the most common CADRs [22]. A study from south India also showed cutaneous as the common type of ADRs [23].…”
Section: Discussioncontrasting
confidence: 75%
“…In contrary to this study, urticaria forms the most common CADRs [22]. A study from south India also showed cutaneous as the common type of ADRs [23].…”
Section: Discussioncontrasting
confidence: 75%
“…According to the anatomical system, the skin was the chief organ system affected. Various previous studies by James et al, Lihite et al, and Ramakrishnaiah et al showed the involvement of skin as the chief organ system was affected with the most common complaints of skin rashes [1,8,19].…”
Section: Discussionmentioning
confidence: 95%
“…In another study conducted in South India, the ADRs were most frequently reported in the adult age group (75%), with a slight female preponderance (60%). Antibiotics contributed to the maximum number of ADRs, followed by analgesics [10]. Another study from the same region found that most of the ADRs were in females (60%).…”
Section: Mirmentioning
confidence: 91%